Risk analysis for rwh system and its verification by mathematical methods - Karelová, Zuzana; Vranayová, Zuzana; Káposztásová, Daniela; Purcz, Pavol (Видавництво Львівської політехніки, 2013)
Rainwater is an alternative and sustainable so urce of water which is in compliance with the idea of sustainable development. Risk analysis helps us to identify the risks associated with the rainwater harvesting (RWH) in general. In th is article we identify that parts of the RWH system where potential hazardous events coul d occur. The potential hazardous events are evaluated by risk analysis and the most hazardous parts of the system are designated. Well known Water Safety Plan and semi-quantitative approach was used as a template for risk analysis. This method was verified by various mathematical methods as described in this article. Дощова вода є aльтернативним і відновлювальним джерелом води та відповідає ідеям збалансованого розвитку. Аналіз ризиків дозволяє ідентифікувати ризики, пов’язані зі збором дощової води (RWH) в цілому. Визначено, що частини системи збору дощової води є потенційно небезпечними. Потенційні небезпеки були оцінені шляхом аналізу ступенів ризику і найбільш небе зп ечні частини системи були встановлені. Як зразок для аналізу використано відомий План Безпеки Води (Water Safety Plan) і напівкількісний підхід. Методика була перевірена різними математичними методами.
Keywords: rainwater harvesting (RWH); stormwater management; risk analysis; semi-quantitative method; збір дощової води (RWH); аналіз ступеня ризику; напівкількісна методика